Reformasi Kebijakan Impor Bahan Bakar Minyak (BBM) di Indonesia melalui Studi Komparatif dengan Singapura - Dzakiyya Ikbar, Rahajeng; Filippo Taufik, Harven; Rahayu, Delia Sita (Dinasti Research, 2026)
Indonesia’s fuel import policy in recent years has shown a tendency toward centralization through coordinated mechanisms, quota restrictions, and shortened licensing periods, raising concerns regarding fair competition principles and consumer protection. In this context, an evaluation of fuel import regulations is necessary to ensure supply security without creating market distortions. This study employs a normative juridical method using functional comparative and law-in-context approaches to examine how administrative norms operate within different market structures and institutional frameworks. Indonesia’s regulatory framework is compared with that of Singapore, which applies a non-exclusive licensing regime, stringent technical standardization, and active competition oversight. The comparison demonstrates that supply stability and quality assurance can be achieved through open market access combined with technical supervision and effective enforcement of competition law. Reform of Indonesia’s fuel import policy should therefore move toward a non-exclusive licensing system based on objective criteria, enhanced transparency in the commodity balance mechanism, formal involvement of the competition authority in policy evaluation, and strengthened quality control mechanisms through independent certification and sampling.